2007
DOI: 10.1590/s1517-83822007000400034
|View full text |Cite
|
Sign up to set email alerts
|

Production of moderately halotolerant, SDS stable alkaline protease from Bacillus cereus MTCC 6840 isolated from lake Nainital, Uttaranchal state, India

Abstract: A moderately cold active, extracellular alkaline protease producing bacterium was isolated from a fresh water lake. The isolate was found to be a gram-positive, rod shaped organism later identified as Bacillus cereus MTCC 6840. The bacterium produced the maximum amount of enzyme when allowed to grow for 24 h at temperature 25º and pH 9.0. Among a variety of substrates used, fructose as a carbon source and a combination of yeast extract and peptone as nitrogen source, supported the maximum protease production b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 21 publications
5
27
0
Order By: Relevance
“…The treatment with SDS in the concentration range of 0.05 to 0.6 % retained the protease activity from B. megaterium MTCC 2444 in the range of 70 to 75 % (Fig.12). These results were similar to the activity of protease of B. cereus MTCC6840 at 1 % concentration of SDS (Joshi et al 2007). In contrast, VM10 protease showed 60 to 65 % activity towards 0.05 to 0.4 % SDS concentration (Venugopal and Saramma 2008).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The treatment with SDS in the concentration range of 0.05 to 0.6 % retained the protease activity from B. megaterium MTCC 2444 in the range of 70 to 75 % (Fig.12). These results were similar to the activity of protease of B. cereus MTCC6840 at 1 % concentration of SDS (Joshi et al 2007). In contrast, VM10 protease showed 60 to 65 % activity towards 0.05 to 0.4 % SDS concentration (Venugopal and Saramma 2008).…”
Section: Resultssupporting
confidence: 84%
“…2). Similar results were reported for the protease production by B. subtilis BS1 (Shaheen et al 2008), whereas the optimum pH of 9.0 and 10.5 were recorded for B. cereus MTCC6840 and B. circulans, respectively (Joshi et al 2007;Jaswal et al 2008). The optimum incubation time was 48 h (Fig.…”
Section: Resultssupporting
confidence: 76%
“…Thus YE served to be a better nitrogen source for protease and lipase production than peptone. Joshi et al (9) have reported a combination of both YE and peptone as a better source for protease production by Bacillus cereus.…”
Section: Resultsmentioning
confidence: 99%
“…Heat stable protease production at 25 o C from a psychrotrophic P. fluorescens RO98 was reported by Koka and Weimer [97]. Joshi et al [86] reported maximum protease production at pH 9.0 and 25 o C from Bacillus cereus MTCC 6840 isolate. Kasana and Yadav [85] reported thermoalkalistable protease from a psychrotrophic Exiguobacterium sp.…”
Section: Alkaline Proteases From Psychrophiles/psychrotrophsmentioning
confidence: 69%
“…The protease retained 78% activity even in the presence of 20% NaCl [180]. An alkaline protease of halotolerant B. cereus MTCC 6840 exhibited 100% stability in the presence of 5% NaCl [86], and showed good activity in the range of 6-10% (w/v) NaCl concentrations. An [180,181].…”
Section: Alkaline Proteases From Halophilesαmentioning
confidence: 99%